Determination Tourism Village Economy: Does Covid-19 Have An Impact On Pades And Village Community Income? - Devi Febrianti; Suryani Yuli Astuti (Universitas Muhammadiyah Malang, 2023)
Purpose: This research was developed to analyze the things that can determine the economy of a tourism village affected by Covid-19 in Lamongan Regency in terms of PADes and Village Community Income. Methodology/approach: This research uses qualitative by using case study approach. Findings: These findings imply that the existence of this tourist village can help the surrounding community in getting jobs. In addition, it can help the community in increasing people's income and PADes. At the time of Covid, there was decrease in PADes and income for the Labuhan Tourism Village, except Kendal because their marketing strategy was quite good. Practical and Theoretical contribution/Originality: There is a tourism village contribution in terms of PADes and village community income. The results of this study can be used by the government as material for consideration in improving implementation, especially Permendagri No 66 Tahun 2007, especially village development planning to face of Post-Covid 19. Research Limitation: This research was only conducted in the largest PADes recipient villages. This should be done in tourist villages that receive the largest and smallest PADes so that they can see more deeply the impact of Covid-19 on each village.